Study of the influence of air holes along length of convergent-divergent passage of a venturi device on aeration - Emiroglu, ME; Baylar, A (Int Assn Hydraulic Research, 2003)
One of the most cited water quality parameters in the freshwater hydrosphere is dissolved oxygen. The oxygen concentration in surface waters is a prime indicator of the quality of that water for human use as well as use by the aquatic biota. When a water jet impinges a pool of water at rest, air bubbles may be entrained and carried a way below the pool free surface. This process is called plunging water jet entrainment and aeration. In this paper, air entrainment rate and oxygen transfer efficiency of venturi device with air holes along the length of the convergent-divergent passage was studied experimentally, and in particular, the effect of varying numbers, positions, and open/close status of the air holes. A negative pressure drew air in through holes at the convergent-divergent passage of the venturi device. This phenomenon affected the water jet expansion, the air entrainment rate, and the bubble penetration depth and hence the oxygen transfer efficiency. It was demonstrated that the values of air entrainment rate and the oxygen transfer efficiency of the venturi device were significantly higher than those of the circular nozzle.
Étude de l'influence sur l'aération d'un dispositif de trous d'aération le long du convergent-divergent d'un venturi
Keywords: air entrainment rate; dissolved oxygen; aeration; water jet; venturi; nozzle